STUDI ANALISIS KURIKULUM ILMU FALAK UIN ALAUDDIN MAKASSAR BERBASIS INTEGRASI ASTRONOMI - Primantyas, Bagus Herdianto; Wakia, Nurul; HR, Sabriadi (Universitas Islam Negeri Alauddin Makassar, 2026)
ABSTRACT This research focuses on analyzing thecurriculumof phalac scienceat theStateIslamic University of Alauddin Makassar based on astronomy integration. Theformulation of this problemincludes: how is thecurriculumof phalac scienceat Alauddin Makassar StateIslamic University, how is theastronomical integration of thecurriculumof phalac scienceat Alauddin Makassar StateIslamic University. This research uses a library research method by analyzing theastronomy integration-based astrophysics curriculumthrough sources obtained frombooks, articles, theses, and reports on previous research results that arerelevant to this research. Theresults of this study aretherealistic learning of astrophysics applied by theFalak ScienceStudy Programat Alauddin Makassar StateIslamic University has 63 courses with 147 credits consisting of 13 University compulsory courses, 22 Faculty courses and 26 Falak ScienceStudy Programcourses. Of the26 courses in theFalak ScienceStudy Programthat need to beadded are13 courses, namely Lunar EclipseHisab, Solar EclipseHisab, Non-Optic Rukyat Devices, Optical Rukyat Devices, Advanced Falak ScienceText Studies, Hisab and Rukyat Practices, Basics of Astronomy, Basics of Spherical Astronomy, Basics of Physics, Mathematics. Hisab Rukyat Study of Different Countries, Astronomy and Culture, Calculator Algorithms and Programming, Computer Algorithms and Programming (Excel), Computer Algorithms and Programming (VB and Android), and Statistics. Theimplication of this research is that theFalak ScienceStudy Programis expected to reducelegal courses to fit thefocus of theacademic field and review or review theexisting curriculumat other universities. Keywords: Astronomy Integration, Curriculum, Falak Science